PENGARUH AKUNTABILITAS, TRANSPARANSI PENGELOLAAN KEUANGAN DESA DAN PARTISIPASI MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT PADA DESA DI KECAMATAN SIMO KABUPATEN BOYOLALI - Anggraeni, Dhita Dewi; Theorupun, Milka Susana; Triatmaja, Nur Asih (EKOBIS, 2023)
This study aims to determine the effect of accountability, transparency of village financial management and community participation on community welfare. The research was conducted in 13 villages in Simo District, Boyolali Regency which were distributed to village officials who knew financial reports. The sample in this study used a purposive sampling technique with a total sample of 200 for the 2018-2022 period. The data in this study were obtained by distributing questionnaires which were filled in directly and supporting data in the form of APBDes realization reports. The analytical method uses multiple regression analysis with the help of the SPSS application. The results of this study are accountability, transparency of village financial management and community participation which have a significant and partially positive effect on community welfare. Meanwhile, accountability, transparency of village financial management and community participation have a significant and positive effect simultaneously on community welfare.